Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2168.1998.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of adhesion formation in open and laparoscopic fundoplication

Abstract: These findings indicate that laparoscopic fundoplication in rats leads to less severe adhesions of a different type (parietal) compared with those seen in the open controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 21 publications
2
34
1
5
Order By: Relevance
“…83 observaram menor formação de aderências no grupo submetido à laparoscopia quando comparado à cirurgia convencional, de forma que no primeiro grupo as aderências eram predominantemente parietais e mais finas, enquanto que no segundo, eram predominantemente viscerais e mais espessas.…”
Section: Impacto Da Via De Acesso Na Prevenção De Aderênciasunclassified
“…83 observaram menor formação de aderências no grupo submetido à laparoscopia quando comparado à cirurgia convencional, de forma que no primeiro grupo as aderências eram predominantemente parietais e mais finas, enquanto que no segundo, eram predominantemente viscerais e mais espessas.…”
Section: Impacto Da Via De Acesso Na Prevenção De Aderênciasunclassified
“…If different types were present, the highest type was scored. The severity of adhesion formation was calculated by multiplying extent and type of the adhesions [10, 21]. Regrowth is defined as new (recurrent) adhesion formation at sites, where adhesions were present at first evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, clinical and experimental studies have shown fewer adhesions after laparoscopic operations as compared with the open technique [6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…17,[19][20][21][22][23][24][25][26] In this study most patients (94.4%) have a history of laparotomy. However there are not significant differences in PAI score based on previous surgical access (open vs laparoscopic, P=0.352).…”
Section: Figure 1 Peritoneal Adhesion Index (Pai)mentioning
confidence: 99%